Genotypic and Phenotypic Characterization of IncX3 Plasmid Carrying blaNDM-7 in Escherichia coli Sequence Type 167 Isolated From a Patient With Urinary Tract Infection - Hao, Yingying; Shao, Chunhong; Bai, Yuanyuan; Jin, Yan (Frontiers in Microbiology, 2018)
Infections due to New Delhi metallo-beta lactamase (NDM)-7-producing Escherichia coli are infrequent and sporadic. In this study, we report one case of recurrent urinary tract infection caused by blaNDM-7-producing E. coli belonging to phylogenetic group A, sequence type (ST) 167. In this study, we aimed to describe the genotype and phenotype of blaNDM-7-producing E. coli in China. The isolate exhibited resistance to β-lactam antimicrobials, trimethoprim-sulfamethoxazole, quinolones, and aminoglycosides. blaNDM-7 is located on a conjugative plasmid designated pJN05NDM-7 belonging to type IncX3. pJN05NDM-7 was fully sequenced and compared with all publicly available blaNDM-7-harboring plasmids. pJN05NDM-7 is almost identical to pKpN01-NDM7 and pKW53T, although the plasmids are geographically unrelated. The comparison of IncX3 plasmids harboring blaNDM in China showed high similarity, with genetic differences within insertion fragments. Notably, the differences in plasmids of animal and human origin were insignificant, because only one plasmid showed deletion inside the ISAba125 region compared with pJN05NDM7 . Our study demonstrates that E. coli carrying IncX3 plasmids play an important role as a reservoir and in the spread of blaNDM. Further studies should be performed to control the dissemination of blaNDM among food animals.